MicroRNA-107 Regulates Adiponectin Expression and Human Adipocyte Differentiation - Ahonen, Maria (My University, 2019)
Adiponectin (AdipoQ) is a major adipokine with insulin-sensitizing and anti-inflammatory effects. AdipoQ expression is downregulated in obesity, insulin resistance and type 2 diabetes. In this study, we investigated the effect of microRNA-107 (miR-107) on AdipoQ expression. miR-107 is a known regulator of insulin sensitivity and Caveolin 1 of Caveolin 1 / adiponectin receptor 1 complex. Furthermore, miR-107 is upregulated in insulin resistance. Differential microRNA expression has been shown to be behind many pathophysiological changes in metabolic diseases. Thus, we wanted to investigate whether miR-107 regulates AdipoQ expression and the mechanism behind the regulation. Our results show that AdipoQ is substantially downregulated by miR-107 overexpression in Simpson-Golabi-Behmel syndrome adipocytes, transfected at the preadipocyte stage. In addition, adipocyte differentiation was markedly reduced upon miR-107 transfection, demonstrated by a reduction in triglyceride storage, lipid droplet accumulation and adipocyte differentiation gene markers. AdipoQ was also downregulated, although not as robustly, in adipocytes transfected at the mature stage. In silico analyses and Luciferase-AdipoQ 3’UTR reporter assays suggested that miR-107 is likely to regulate AdipoQ indirectly. The data indicates that miR-107 mediates its effects on AdipoQ expression via downregulating HIF-1β, an inducer of AdipoQ expression, and increasing FOS, a suppressor. In conclusion, miR-107 was identified as a novel regulator of AdipoQ. Taken together, the results show that miR-107 inhibits AdipoQ through indirect mechanisms, both by dampening adipocyte differentiation and by affecting its regulation in mature adipocytes.